Making ‘Ethical Hindus’: Sanskrit Traditions, Oral Performance, and Hindu Nationalism in Contemporary India - Alder, Ketan (Religions of South Asia, 2018)
This article considers the intersections between Hindu nationalist Sanskrit traditions and notions of ethical Hindu selfhood. Its main material is drawn from ethnographic research in Hindu-nationalist-affiliated schools in the central Indian state of Jharkhand. In examining the interweaving of mantras and stotras into school life, this article shows how the daily enactment of Hindu nationalist Sanskrit traditions constructs a register from which can be drawn a disciplinary experience of Hinduism, together with an ordered Hindu society: Hindu sangathan. In further analysing the emergence of Hindu identities in Sanskrit traditions at the margins of Hinduism, my research demonstrates the development of Hindu representation outside of juridical languages of rights. Instead, I illustrate its formation as a detailed task of ethical reform. In pointing toward the efficacy of oral Sanskrit traditions in constituting ethical identities, this article contributes to scholarship which foregrounds models of action which cut across liberal secular conceptual categories of public/private, and reason/emotion.